Evaluation of Yield and Quality of Three Jackfruit (Artocarpus heterophyllus L.) Genotypes - Rahman, M H; Alam Patwary, M M; Barua, H; Nahar, S; Noman Faruq Ahmmed, Abu (The Agriculturists, 2016)
Yield and quality performances of three jackfruit genotypes were studied at the Agricultural Research Station, Bangladesh Agricultural Research Institute, Pahartali, Chittagong during 2013-2014. Age, growth, maturity period, yield potential and also qualitative characteristics were compared among them. Based on overall performance with respect to bearing potential, maturity period, fruit and bulb characters, the genotypes AHPah-1 have been found promising for table purpose followed by AHPah-2 and AHPah-3. Minimum days (117) to 1st harvest were observed in AHPah-1. The number of fruits per plant was exceedingly higher (73) in AHPah-1 whereas minimum number (41) was found in AHPah-2. Maximum weight (8.40 kg) per fruit was observed in AHPah-2 and minimum was in AHPah-1(3.40 kg). The highest single fruit length (37.25cm) was found in AHPah-2 and breadth (27.00cm) was produced by AHPah-3. Maximum number of bulbs (116) was produced in AHPah-1, whereas minimum (63.00) was in AHPah-3. Maximum weight of bulbs per fruit (4.24 kg) was produced in AHPah-2. Individual bulb weight was higher (54.42g) in AHPah -2 whereas, the lowest (16.71) was in AHPah-1. Edible portion was higher (69.27%) in AHPah-1 whereas, the lowest (53.43%) was in AHPah-3. The TSS was the highest (21.00%) in AHPah-1. The highest bulb length and breadth was found in AHPah-3. Highest seeds weight (639g) was produced in AHPah-2. Individual seed weight (8.19 g) was higher in AHPah-2. Therefore, the genotypes can be included in the variety development program after comparing with the already BARI released jackfruit variety. The Agriculturists 2016; 14(1) 107-111